Sanctuary of the shadow ebook - Ascher, Aurora (Elemental Emergence, 2024)
The instant New York Times bestseller A Refinery29 Most Anticipated Book of 2024 "Ascher's latest is a fantasy romance that has everything nice—a hot love interest, a relatable main character, female friendship—and plenty of (consensual) spice." ― Booklist Some follow their destiny. Others fall for it. For humans, Salizar's is a place of mystery and wonder. For Harrow, it's a place to hide from those who slaughtered her entire clan. A haven where she can disguise both her abilities and who she really is. Until he arrives. He has no recollection of who—or even what —he is. He only knows that he's a monster, with wings and powerful abilities never seen before. But beneath the layers of rage and isolation, one glimpse into those inky black eyes reveals a soul that calls out to the loneliness in Harrow. And so she chooses him. She is drawn to the mystery of him, her unquenchable need for his kiss. And as powerful enemies align and conspire against them, Harrow knows their only hope is escape. Now, with every secret she unlocks from his past, a shadow from her own whispers free—luring enemies who will stop at nothing to get their final revenge on Harrow. And she's given them the perfect weapon...because her winged beast is not what he seems. But maybe it's time they finally learn—neither is she.